PENGARUH EKSTRAKURIKULER KARET TERHADAP PENDIDIKAN KARAKTER SISWA SEKOLAH DASAR 001 SANGATTA UTARA: - Fitri Nur Jannah Fitri; Dhiniaty Gularso (STKIP Subang, 2025)
This study aims to determine the influence of extracurricular activities implemented in elementary schools on the formation of student character. The type of research used in this study is library research from previous research. The method used in this study is qualitative. Data collection in this study was carried out through literature studies from journals, books, and other sources that have been recognized for their accuracy. The results of this study analysis indicate that there is a visible influence of extracurricular activities on the character of students in elementary schools. Through extracurricular activities, students can develop their character and talents.